Asymptomatic bacteriuria persisting after catheter removal: are we missing the true catheter associated urinary tract infection burden? - Simran; Ujjwala Gaikwad; Sabah Siddiqui (Journal of Infection in Developing Countries)
Introduction: Catheter Associated Asymptomatic Bacteriuria persisting beyond 48 hours after catheter removal predisposes to the development of catheter associated urinary tract infections, necessitating treatment. Current surveillance strategies do not screen for infection detection after catheter removal, missing most of the clinically significant catheter associated urinary tract infection cases.